The Tumor Suppressor BCL7B Functions in the Wnt Signaling Pathway - Uehara, Tomoko (PLoS Genet, 2015)
Human BCL7 gene family consists of BCL7A, BCL7B, and BCL7C. A number of clinical studies have reported that BCL7 family is involved in cancer incidence, progression, and development. Among them, BCL7B, located on chromosome 7q11.23, is one of the deleted genes in patients with Williams-Beuren syndrome. Although several studies have suggested that malignant diseases occurring in patients with Williams-Beuren syndrome are associated with aberrations in BCL7B, little is known regarding the function of this gene at the cellular level. In this study, we focused on bcl-7, which is the only homolog of BCL7 gene family in Caenorhabditis elegans, and analyzed bcl-7 deletion mutants. As a result, we found that bcl-7 is required for the asymmetric differentiation of epithelial seam cells, which have self-renewal properties as stem cells and divide asymmetrically through the WNT pathway. Distal tip cell development, which is regulated by the WNT pathway in Caenorhabditis elegans, was also affected in bcl-7-knockout mutants. Interestingly, bcl-7 mutants exhibited nuclear enlargement, reminiscent of the anaplastic features of malignant cells. Furthermore, in KATOIII human gastric cancer cells, BCL7B knockdown induced nuclear enlargement, promoted the multinuclei phenotype and suppressed cell death. In addition, this study showed that BCL7B negatively regulates the Wnt-signaling pathway and positively regulates the apoptotic pathway. Taken together, our data indicate that BCL7B/BCL-7 has some roles in maintaining the structure of nuclei and is involved in the modulation of multiple pathways, including Wnt and apoptosis. This study may implicate a risk of malignancies with BCL7B-deficiency, such as Williams-Beuren syndrome.